On the interoperability performance of HBIM models for structural conservation and upgrading of building aggregates in the Italian minor centres - Adriana Marra; Giovanni Fabbrocino; Ilaria Trizio (Vitruvio: International Journal of Architectural Technology and Sustainability)
The article deals with the definition and evaluation of a workflow to demonstrate that the parametric model of a historic building with a high level of digital maturity can be configured as a tool that fosters collaboration between the various professionals involved in the recovery and rehabilitation process of historic buildings. It also represents the starting point for developing structural models for quantitative analyses. The implementation of HBIM to the building aggregate called “La Giudea” in Santo Stefano di Sessanio (AQ), an artefact that is particularly representative of the historical building heritage of the small medieval village in the Abruzzo Inner Areas, has provided a model for managing the information deriving from the knowledge process. The model delivers to the use of the state of conservation, and it represents the base for the structural analysis of the asset and the identification of the measure and interventions for its preservation. The parametric model was developed in the design of strengthening and restoration works requiring interactions between digital environments. In such a framework, an investigation aimed at evaluating the interoperability of the digital model and particularly the vertical interoperability between different software packages has been explored.